Incidence of accidents by scorpions in the State of Alagoas, northeast of Brazil (Research, Society and Development, 2022)
Scorpions are among the most important venomous animals, due to the high frequency with which they occur and their potential severity, especially in children, being considered a public health problem. In Brazil, scorpion accidents surpass snakebites. In this sense, the present article aimed to know the incidence of cases of poisoning caused by scorpions, in the State of Alagoas, during the period from 2018 to 2021. This is a descriptive and retrospective qualitative-quantitative study, using secondary data collected in the official SINAN Net database. During the study period, 40,590 accidents by scorpions were reported, the year 2021 had a higher record of cases with 10,766 cases. Of the 102 municipalities, eight (08) of them had the highest incidence, of these municipalities, Maceió with the highest occurrence, 17,512 cases and Marechal Deodoro with the lowest number, 918 cases. It was found that scorpion accidents have a uniform distribution during all months of the year. In the four years, females were the most affected, registering 59% of accidents. The predominant age group was 20-49 years old, compatible with the economically active population. It is concluded that the State of Alagoas presented a similar profile between the years studied and also a very close scenario, when compared with other studies carried out in other regions of the country.